Dumpster Diving Threat In Personal Data Leakage Case In Indonesia Social Contracts Undertaken by the State in Post-Pandemic - Michael, Tomy (Operations Research: International Conference Series, 2023)
Justice in the legal context is to bring out a caring attitude from the state and this is important in the post-pandemic era. The state has the ability to exercise control over all things as its natural state but must still pay attention to the condition of society. Justice must be an inseparable part of a country because of the existence of a social contract from society. The research object is a country with a normative research method that makes legal hermeneutics a problem solving. As a result, the state cannot impose its will in the post-pandemic era because the people have done what the people want, including vaccines, using masks or maintaining attitudes in daily life. The conclusion obtained is that there is a prioritization of the meaning of the social contract so that the essence of justice appears and has a good impact on society.